Parental conflict and young adult romantic relationships: the role of sibling relationship quality - Fihn, Gabrielle, author; Quirk, Kelley, advisor; Lucas-Thompson, Rachel, committee member; Faw, Meara, committee member (Colorado State University. Libraries, 2018)
Romantic relationship development and maintenance contributes to the overall well-being and psychological health of partners. Decades of research has indicated that parental divorce is negatively associated with psychological adjustment and romantic relationship outcomes later in development. More current research, however, claims that divorce alone does not account for the variability in these outcomes, and that multiple subsytems within the family unit are likely influential. The proposed study aims to examine one family subsystem, sibling relationships, on the association between young adult romantic relationship outcomes and parental conflict and divorce. Three hundred and thirty two young adults provided responses to questions about their parent relationship quality, sibling relationship quality, and four romantic relationship outcomes (attitudes, relationship commitment, relationship satisfaction, relationship confidence). A linear regression and a moderation test were conducted to examine the associations between sibling relationship quality, parental conflict, and the outlined romantic relationship outcomes. Results revealed support for the powerful association that siblings play in young adults romantic relationship formation and satisfaction. Implications are offered for future studies in this important line of work.